Referee positioning, but not match demands, score difference, or field location, are associated with breakdown decision-making accuracy in elite rugby sevens referees - SantAnna, R. T.; Roberts, S. P.; Moore, L. J.; Stokes, K. A. (International Journal of Performance Analysis in Sport, 2021)
This study quantified rugby referees` decision-making accuracy at the breakdown in an elite rugby sevens tournament, examining whether decision-making accuracy differed over time, and if it was associated with match demands, score difference, field location, and referee positioning. During the National Sevens Tournament (six referees, 22 matches), decision-making accuracy was analysed using video coding from 602 breakdowns and match demands were examined using GNSS technology and heart rate recordings. Overall, the referees had a decision-making accuracy of 88.2% with no changes over time (all p > 0.05). There were no significant associations between match demands, score difference, or field location and decision-making accuracy (all p > 0.05). However, significantly more incorrect decisions occurred when the referees were in a suboptimal position (29.0%) compared to an optimal position (10.9%) at the breakdown (p < 0.05). The findings suggest that referees` decision-making accuracy during the breakdown remains relatively consistent across an elite rugby sevens tournament. While unaffected by match demands, score difference or field location, referees` decision-making accuracy may be improved by optimising their positioning at the breakdown.